Early Development Drives Variation in Amphibian Vulnerability to Global Change - Brooks, George C.; Kindsvater, Holly K. (Frontiers in Ecology and Evolution, 2022)
Understanding how natural selection determines species’ life histories can reveal their resilience or sensitivity to anthropogenic changes. For example, the safe harbor hypothesis posits that natural selection will favor life-histories that maximize the time spent in the safest life stages; a second theoretical prediction suggests that species with complex life histories will maximize the growth potential of a life stage relative to its safety. Amphibians exhibit complex life-histories, with a diversity of developmental strategies occurring across taxa. Many strategies involve the complete elimination of a particular life stage, and thus provide an excellent opportunity to evaluate the main tenets of the safe harbor hypothesis and understand the consequences of this developmental variation for conservation of threatened amphibians. We develop a general framework for understanding developmental life-histories of amphibians – including the special cases of paedomorphism, direct development, and viviparity - based on the relative growth potential and safety offered by aquatic and terrestrial habitat, which we tested using a global trait database. We then compare the IUCN Red List status of species differing in developmental mode, revealing that most fully aquatic species and species with an aquatic larval stage are currently of Least Concern, despite the fact that freshwater habitats are being lost at a much faster rate compared with terrestrial ecosystems. The higher proportion of direct developing and viviparous species that are threatened can be attributed to their smaller ranges, the fact that they are more likely to be found in rainforest habitats, and their relatively slow life histories. We conclude that an amphibian’s developmental mode reflects the relative costs and benefits of different habitats, and that this could contribute to the resilience or vulnerability of amphibians to future anthropogenic change.